Auxin controls seed dormancy through stimulation of abscisic acid signaling by inducing ARF-mediated ABI3 activation in Arabidopsis - Liu, Xiaodong (National Academy of Sciences, 2013)
The transition from dormancy to germination in seeds is a key physiological process during the lifecycle of plants. Abscisic acid (ABA) is the sole plant hormone known to maintain seed dormancy; it acts through a gene expression network involving the transcription factor ABSCISIC ACID INSENSITIVE 3 (ABI3). However, whether other phytohormone pathways function in the maintenance of seed dormancy in response to environmental and internal signals remains an important question. Here, we show that the plant growth hormone auxin, which acts as a versatile trigger in many developmental processes, also plays a critical role in seed dormancy in Arabidopsis. We show that disruptions in auxin signaling in MIR160-overexpressing plants, auxin receptor mutants, or auxin biosynthesis mutants dramatically release seed dormancy, whereas increases in auxin signaling or biosynthesis greatly enhance seed dormancy. Auxin action in seed dormancy requires the ABA signaling pathway (and vice versa), indicating that the roles of auxin and ABA in seed dormancy are interdependent. Furthermore, we show that auxin acts upstream of the major regulator of seed dormancy, ABI3, by recruiting the auxin response factors AUXIN RESPONSE FACTOR 10 and AUXIN RESPONSE FACTOR 16 to control the expression of ABI3 during seed germination. Our study, thus, uncovers a previously unrecognized regulatory factor of seed dormancy and a coordinating network of auxin and ABA signaling in this important process.